(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article provides strategies for increasing the competitiveness of textile industry enterprises, effective organization of strategic actions, their development and promotion. The problems existing in the industry were analyzed as a result of the study of regulatory documents and statistical data on textile support. As a result of the analyzes carried out by the author, a number of proposals and comments were made for the development of enterprises through the strategies of increasing competitiveness, increasing the sales volume and quality of products, and gaining a place in the world market.